Публічно-приватне партнерство як механізм розвитку сільських територій - Ільїна, М.В.; Шпильова, Ю.Б. (Економіка природокористування і сталий розвиток, 2019)
Розкрито сутність, функції та особливості застосування публічно-приватного партнерства для розвитку місцевої економіки. Визначено напрями інституціоналізації публічно-приватного співробітництва та його роль у забезпеченні сталого розвитку сільських територій. Розроблено механізм державної підтримки такого партнерства та організаційно-економічні етапи його запровадження на місцевому рівні в сучасних умовах. Public-private partnership is the instrument of cooperation between state and business. It has many forms and functions but the only purpose to improve welfare of the territories. In relations between state and business the partnership can play dominant, subsidiary or supervisory role, regulate the institutional mechanism of financial cooperation, develop strategies, solve conflicts and provide social, communal and infrastructure services.
Currently implementation of the public-private partnership mechanism in Ukraine is complicated because of shortcomings and gaps in legislation, deficit of different levels budgets, institutional inability of local governments to plan and implement partnership projects and low efficiency of economic activity of business entities. Concerning implementation of the mechanism on rural areas it should be substantially enhanced at the national level for many reasons. Firstly economic situation in most rural areas in Ukraine is depressed and community budgets lack funds. It proves the necessity to intensify economic cooperation and introduce other forms of cooperation. On the other hand, many negative socio-demographic trends (migration, depopulation, social exclusion and marginalization) are inherent in rural areas. It makes difficult for local governments to cooperate with communities members. Capability of the state to support partnerships is also complicated major because of underdeveloped organizational and economic support mechanism. Lack of annual plans to finance partnership projects, funds, technical support to implement projects, and no ways to get state guarantees are the evidence.
Taking into account rural territories have no much capacity for development, the mechanism of public-private partnership should include the following key steps: identifying priority areas for PPP application, considering socio-economic potential of different types of the territories and social relevance of a project for a community; improving the qualification level of project management personnel; involvement of the private sector into infrastructural projects; state support for pilot projects; ensuring more transparency in decision making and use of budget resources and simplifying project selection requirements. Implementation of the PPP mechanism on rural areas will improve their infrastructure and satisfy social needs of residents. In order to improve the mechanism of state support for the implementation of PPP projects at the local level it is needed to establish a national specialized agency, define clearly powers of the state authorities, local self-government authorities and members of communities involved into PPP implementation. The other task is to create an informational framework.
The purpose of the article is to substantiate how the public-private partnership’s mechanism can work on rural areas.